Numerical investigation of forced convective heat transfer around a solid circular cylinder utilizing nanofluid in unsteady regime - Khelili, Yacine (Array, 2019)
This paper presents a numerical solution for low Reynolds number, unsteady flow around, and heat transfer from a stationary circular cylinder placed in a uniform flow. The fluid is assumed to be incompressible and of constant property. Twodimensional and unsteady mass continuity, momentum, and energy equations have been discretized using finite volume method. A SIMPLE algorithm has been applied for solving the pressure linked equations. The range of Reynolds numbers was investigated which varied from 50 to 300 with volume fraction on Cu nanoparticles varying from 1 to 5 % at the constant wall temperature. The results of the heat transfer characteristics of nanofluid flow over a circular cylinder showed marked improvement comparing with the base fluid. It is found that the vorticity, pressure coefficient, and recirculation length are increased by the addition of nanoparticles into base fluid. Moreover, the local and mean Nusselt numbers are enhanced due to adding nanoparticles into base fluid.